Assessment of the Potential Anti-tumour Effect of Salvia triloba and the Combination of Salvia triloba and Paclitaxel on Ovarian Cancer: SKOV3 Cell Line - Saleh, Naela (AUC Knowledge Fountain, 2021)
Abstract Cancer remains one of the most lethal diseases in the world, and ovarian cancer is the primary cause of mortality among gynecologic cancer cases. Most existing chemotherapies, when applied individually and separately, are both toxic and non-effective. Herbal plants have been studied for decades to be employed in anti-cancer medication due to their efficacy. Salvia triloba, generally known as Greek Sage, has been traditionally used in the Middle East for medical treatment. There have been recent studies associated with the anti-cancer ability of Salvia triloba against both breast cancer and skin cancer. However, no evidence has been found for a study that associates Salvia Triloba with anti-cancer ability for ovarian cancer. In this study, we investigated the anticancer effects of Salvia triloba using SKOV3 ovarian cancer cell line. Cell viability and cell migration were both studied through applying Salvia triloba acetone crude extract as a single treatment and, as well, in combination with Paclitaxel, using MTT, Trypan Blue Exclusion test of cell viability, and Trans-well assays. Gene expression was also studied using quantitive PCR. The CompuSyn software was used to obtain data regarding the type of combination effect. The results obtained proposed that Salvia triloba in combination with Paclitaxel could potentially reduce both cell viability and migration on SKOV3 cell line through controlling the expression of key genes in signaling pathways, which play a critical role in ovarian cancer progression.